Anti - Inflammatory Activity Of Benincasa Hispida Fruit - MA RACHCHH; PN YADAV; RH GOKANI; SM JAIN (International Journal of Pharma and Bio Sciences, 2011)
The present study was designed to investigate anti-inflammatory activity of Petroleum ether and Methanolic extract of Benincasa hispida fruit. Both the extracts at the dose of 300 mg/kg body weight, produced dose dependent and significant inhibition of carrageenan- induced paw edema, histamine induced paw edema and cotton pellet- induced granuloma in rat model. In carrageenan- induced paw edema model, petroleum ether and methanolic extracts showed maximum inhibition in inflammation (0.270 ± 0.063, 0.307 ± 0.043 respectively) as compared to control group (1.27 ± 0.059) which were comparable with standard valdecoxib (0.247 ± 0.033). In histamine-induced paw edema, both the extract showed maximum inhibition (62.86% and 54.84% respectively) as compared to control group, which were comparable with that of standard drug cetrizine (95.24%). Petroleum ether and methanolic extracts showed slight reduction in granuloma tissue formation in cotton pellet implanted rats, which were not significant with that of standard drug diclofenac sodium.